Ulasan Ilmiah : Potensi Pektin Dari Kulit Jeruk Sebagai Emulsifier Melalui Modifikasi Hidrofobik Pektin - Margaretha Hanna Tiffany; Andi Marlisa Bossa Samang; Indrastuti Indrastuti; Syahmidarni Al Islamiyah (Universitas Bumigora, 2023)
Orange peel contains pectin. Pectin is a water-soluble (hydrophilic) polysaccharide compound containing hydroxyl groups. In general, pectin can be used as and emulsifier and can reduces the interfacial tension in water-fat mixture because it has both hydrophilic and hydrophobic sides. However, the emulsion produced by native pectin has low stability, so it needs to be modified. The purpose of this study was to determine the effect of pectin hydrophobic modification on improving the properties of pectin. Hydrophobic modification of pectin using amidation technique which reacts the methoxyl groups in pectin with alkylamine compounds (N-octylamine, N-dodecylamine, and N-octadecylamine) is known to remove the hydrophilic properties of pectin and produce amidated pectin. The results of literature study showed an increase in the affinity of hydrophobic molecules for amidated pectin. In addition, the pectin indicator amidated has the ability to act as an emulsifier in oil and water emulsion systems, which can be proven from the acquisition of interfacial tension values and emulsifying activity. There was a decrease in interfacial tension and an increase in emulsification activity in the modified pectin compared to its native form. This leads to the conclusion that the hydrophobic modification of orange peel can be used as an emulsifier capable of maintaining emulsion system stability. It is hoped that the findings of this review will serve as a resource for readers to conduct additional research as well as a source of information about the hydrophobic pectin modification process.